Development of competencies of leading entrepreneurs in the garment segment of the local productive arrangement in the Pernambuco Agreste - Cabral, Romilson Marques (Revista Econômica do Nordeste, 2016)
The question that guides this paper is: what skills do some entrepreneurs have to meet in order to achieve a leadership position in this area? To support this question we use the Evolutionary Theory of the Firm, in particular, David Teece’s concept framework of economic competencies. This approach focuses on a garment cluster in connection with the attributes of the Transaction Costs Theory. The methodology used in this research is predominantly qualitative. The results indicate that these businesses became local leaders as they developed competencies in procurement activities, product creation, production and sales. The evolution of competencies is considered remarkable in the face of these entrepreneurs’ low schooling level and limited capital resources.